Carbon intercalation efficient snow-melting agent and preparation method thereof

The carbon intercalation high-efficiency snow melting agent prepared through carbon intercalation technology solves the problems of strong corrosiveness and poor ice melting ability at low concentrations, and achieves the effect of efficient ice melting and corrosion reduction.

CN119570446APending Publication Date: 2025-03-07WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738898.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing chlorine-type snow melting agent is corrosive to road facilities and metal materials, and has poor ice melting ability at low concentrations.

Method used

Using carbon intercalation technology, organic matter and molybdenum trioxide are treated in an oil bath in a solution environment to form an intercalated molybdenum trioxide nanosheet, and then carbonized and vulcanized under an inert atmosphere to form a carbon intercalation molybdenum disulfide nanosheet, and mixed it with the chlorine salt solution to remove the solvent by drying to prepare a carbon intercalation high-efficiency snow melting agent.

Benefits of technology

Achieve efficient ice melting ability at low concentrations of chloride salt, while reducing the corrosion effect of chloride ions on the road surface and metals, improving the dispersion of snow melting agents and facilitating application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570446A_ABST
    Figure CN119570446A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon intercalation efficient snow-melting agent and a preparation method thereof, and belongs to the technical field of functional materials and synthesis thereof. The method comprises the following steps: (1) carrying out oil bath treatment on an organic matter and molybdenum trioxide in a solution environment to obtain an intercalated molybdenum trioxide nanosheet; (2) in an inert atmosphere, performing heat treatment on the intercalated molybdenum trioxide nanosheet to complete carbonization, so as to obtain a carbon intercalated molybdenum trioxide nanosheet; (3) in an inert atmosphere, carrying out heat treatment on the carbon-intercalated molybdenum trioxide nanosheet and excessive sulfur to complete a reaction, so as to obtain a carbon-intercalated molybdenum disulfide nanosheet; and (4) adding the carbon-intercalated molybdenum disulfide nanosheet into a chlorine salt solution, and drying to remove the solvent, so that the chlorine salt is loaded, thereby obtaining the carbon-intercalated efficient snow-melting agent. The method has the advantage of convenient process, and the prepared carbon intercalation high-efficiency snow-melting agent utilizes the photo-thermal conversion characteristic of molybdenum disulfide of the carbon intercalation to synergistically enhance the ice-melting capability and slow down the corrosion of the chlorine-type snow-melting agent, and has good popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials and synthesis thereof, in particular to a carbon intercalation high-efficiency snow-melting agent and a preparation method thereof. Background Art

[0002] Snowfall in winter has a huge impact on transportation and life, especially icing on roads, which causes traffic congestion, frequent traffic accidents and inconvenience in travel. In order to ensure smooth roads, snow melting agents are often used to remove ice from roads. Among them, chlorine-type salts (such as sodium chloride, calcium chloride, magnesium chloride, potassium chloride, etc.) snow melting agents are widely used because of their wide sources and low prices. They can quickly reduce the melting point of ice and snow, achieve the effect of rapid melting, and improve road traffic capacity. However, the chloride ions in chloride salt snow melting agents are corrosive to road facilities and metal materials. Long-term use will cause serious damage to infrastructure such as roads and bridges, resulting in an increase in the cost of maintaining facilities. For example, sodium chloride and calcium chloride in chloride salts have a strong corrosive effect on concrete and steel bars, which will cause the concrete protective layer to crack and peel along the direction of the steel bars, reduce the structural bearing capacity, and cause the steel bars to be exposed and rusted; they are also harmful to asphalt gravel paved roads, causing the asphalt surface to peel off.

[0003] Non-chlorine-based (e.g. calcium magnesium acetate, ethylene glycol, etc.) deicing agents can lower the freezing point, improve antifreeze ability, increase the temperature of snow by absorbing moisture, accelerate melting, and form a protective film to prevent snow from recondensing and avoid road icing. It has the characteristics of no pollution and little corrosion to road facilities. However, its deicing efficiency is limited, lower than that of chlorine-based salts, and it has a pungent sour smell and is not widely used. Therefore, it is a development trend to develop a deicing agent with high efficiency and little corrosion to road facilities.

[0004] Currently, the most widely used deicing agent is still based on sodium chloride, and non-chlorine deicing agents have poor deicing ability. The freezing point of sodium chloride solution is -4.3°C when the mass fraction is 7%, and the freezing point can reach -21°C when the mass fraction is 23.3%. However, the deicing rate will decrease at lower temperatures, and increasing the use of sodium chloride will cause serious corrosion to road facilities and metal materials. Therefore, it is of great application significance to develop deicing agents with high deicing ability and the ability to reduce the concentration of sodium chloride. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, in order to solve the problems of strong corrosiveness of chlorine-type deicing agents and poor ice melting ability at low concentrations, in the first aspect of the present invention, a method for preparing a carbon intercalation high-efficiency deicing agent with convenient process is provided, comprising the following steps: (1) Organic matter and molybdenum trioxide are treated in an oil bath in a solution environment to obtain intercalated molybdenum trioxide nanosheets; (2) Under an inert atmosphere, the intercalated molybdenum trioxide nanosheets are carbonized by heat treatment to obtain carbon-intercalated molybdenum trioxide nanosheets; (3) Under an inert atmosphere, the carbon-intercalated molybdenum trioxide nanosheets react with excess sulfur through heat treatment to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Adding carbon-intercalated molybdenum disulfide nanosheets to a chloride-type salt solution, and removing the solvent by drying to complete the loading of the chloride-type salt, thereby obtaining a carbon-intercalated high-efficiency snow-melting agent.

[0006] Preferably, in step (1), the organic matter includes at least one of dodecylamine (DDA), aniline (AN), and tetrabutylammonium hydroxide (TBAOH).

[0007] By using the above-mentioned organic raw materials and subsequently carbonizing the inserted organic matter in situ, the assembly of alternating stacks of MoO3 and carbon layers can be achieved. This two-dimensional hybrid nanostructure has the advantages of many ion-accessible sites, fast electron transmission speed, and good structural stability, which helps to improve the comprehensive performance of snow-melting agents.

[0008] Further preferably, the molar ratio of the organic matter to molybdenum trioxide is 0.1-1:1.

[0009] Those skilled in the art can adopt appropriate solvent types and amounts based on actual conditions to create a solution environment for oil bath treatment. As presented in one or more embodiments of the present invention, solvents such as ethanol are widely available and easy to remove, and are suitable types of choice for this step. In actual operation, technicians can use conventional means such as stirring and ultrasound to promote the dispersion of raw materials when necessary. During the oil bath process, for example, treatment at 80°C for 12 hours allows the organic matter to be dispersed into the interlayer structure of the molybdenum trioxide nanosheets. Technicians can also adjust other treatment temperatures and times to achieve this purpose. Finally, the intercalated molybdenum trioxide nanosheets can be easily recovered by washing, drying or other suitable methods.

[0010] Preferably, in step (2), the inert atmosphere is argon or nitrogen, and the gas flow rate is 10-300 sccm.

[0011] Preferably, in step (2), the heat treatment temperature is 300-500°C and the treatment time is 0.5-2 h.

[0012] After heat treatment under an inert atmosphere, the organic matter in the intercalated molybdenum trioxide nanosheets is in-situ carbonized to conveniently obtain carbon-intercalated molybdenum trioxide nanosheets.

[0013] Preferably, in step (3), the inert atmosphere is argon or nitrogen, and the gas flow rate is 10-300 sccm.

[0014] Preferably, in step (3), the heat treatment temperature is 300-500°C and the treatment time is 0.5-2 h.

[0015] The carbon-intercalated molybdenum trioxide nanosheets react with excess sulfur to form molybdenum disulfide under an inert atmosphere and heat treatment, thereby forming carbon-intercalated molybdenum disulfide nanosheets with a target structure.

[0016] Preferably, in step (3), the carbon-intercalated molybdenum disulfide nanosheets have a size of 1-2 μm and a thickness of 100-200 nm.

[0017] Preferably, in step (4), the concentration of the chloride salt solution is 1 wt.%-7 wt.%.

[0018] Compared with traditional snow-melting agents, when the concentration of the chlorine-type salt solution is controlled under the conditions specified in the present invention, an excellent snow-melting effect can be achieved at a lower concentration load, which helps to reduce the adverse effects of chloride ion corrosion and the like.

[0019] Preferably, in step (4), the chloride salt of the chloride salt solution includes at least one of sodium chloride, calcium chloride, magnesium chloride and potassium chloride.

[0020] Preferably, in step (4), based on the addition amount of the chloride salt solution being 10 mL, the addition amount of the corresponding carbon-intercalated molybdenum disulfide nanosheets is 0.1-10 g.

[0021] Those skilled in the art can use a suitable solvent to dissolve the chlorine salt to prepare the corresponding solution. The chlorine salt in the deicing agent usually has good water solubility, and water has the advantages of being widely available, green and non-toxic, and is therefore a suitable solvent type for this step.

[0022] Preferably, in step (4), freeze drying is used to remove the solvent, so that the chloride-type salt is loaded and a carbon intercalation high-efficiency snow-melting agent is obtained.

[0023] During the freeze-drying process, the material is frozen at low temperatures and then sublimated to remove moisture, avoiding damage to the material structure and loss of performance. Freeze-drying can make the chloride-type salt solution form a uniform film in the carbon-intercalated molybdenum disulfide nanosheets, thereby improving the uniformity of the load. Through freeze-drying, the stability of the obtained carbon-intercalated high-efficiency snow-melting agent can be enhanced, so that it can show better performance in subsequent applications.

[0024] In the second aspect of the present invention, there is provided a carbon intercalated high-efficiency snow-melting agent having high ice-melting ability, reducing the corrosion effect of chloride ions on road surfaces and metal materials, and having good dispersibility. The agent is prepared by the method provided in the first aspect of the present invention.

[0025] Based on the above technical solutions, the design concept and principle of the present invention are as follows: Layered molybdenum disulfide (S-Mo-S) is composed of two sulfur atomic layers sandwiched by a molybdenum atomic layer through van der Waals forces. 4+ It has a strong Coulomb force on chloride ions and has an adsorption effect on chloride ions. In addition, MoS2, as a semiconductor, can effectively absorb light energy and generate electron-hole pairs, improve the photothermal conversion efficiency, and has a fast photothermal response speed, low thermal conductivity, and good stability under photothermal action, all of which help it reduce heat loss in photothermal reactions. Therefore, the present invention utilizes the photothermal properties of MoS2 to melt ice, and forms carbon-intercalated molybdenum disulfide nanosheets through carbonization reaction, so that the Mo-S bond interlayer spacing increases, further improves its photothermal conversion efficiency, and enhances the ice-melting effect. Not only that, traditional chlorine-type salt de-icing agents may aggregate due to moisture absorption or other reasons, which easily causes a decrease in dispersibility. After the chlorine-type salt of the present invention is loaded on the carbon-intercalated molybdenum disulfide nanosheets, it is not easy to gather between the salts due to adsorption, thereby maintaining good dispersibility and facilitating spreading.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for preparing a carbon intercalation high-efficiency snow-melting agent, which has the advantages of convenient process and good prospects for promotion and application.

[0027] The present invention provides a carbon intercalated high-efficiency deicing agent, which maintains a high-efficiency deicing ability under low-concentration chlorine-type salt, and utilizes the adsorption effect of carbon intercalated molybdenum disulfide on chloride ions to slow down the corrosion effect of chloride ions on road surfaces and metals, thereby improving the dispersibility of the deicing agent and facilitating its spreading. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The X-ray diffraction (XRD) pattern of the carbon intercalated high-efficiency snow-melting agent prepared in Example 1; Figure 2 This is a scanning electron microscope (SEM) image of the carbon intercalation high-efficiency snow melting agent prepared in Example 1; Figure 3 The ice melting ability curves of the carbon intercalated high-efficiency snow melting agent and sodium chloride prepared in Examples 1-5; Figure 4 Polarization curves of the carbon intercalated high-efficiency snow-melting agent prepared in Examples 1-5 and sodium chloride in carbon steel. DETAILED DESCRIPTION

[0029] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0030] Example 1 (1) First, 6 mmol of DDA was added to 30 mL of ethanol and ultrasonically treated for 10 min to obtain a uniform solution. Then, 0.6 mmol of MoO3 was added and ultrasonically treated for 30 min. The uniformly mixed solution was heated to 80 °C in an oil bath and stirred for 12 h. After completion, it was cooled to room temperature, washed with ethanol, and dried in a freeze dryer for 24 h to obtain intercalated molybdenum trioxide nanosheets. (2) placing the obtained intercalated molybdenum trioxide nanosheets in an argon atmosphere for heat treatment at an argon flow rate of 100 sccm, heating to 400 °C, and keeping the temperature for 2 h; after completion, naturally cooling to obtain carbon intercalated molybdenum trioxide nanosheets; (3) The obtained carbon-intercalated molybdenum trioxide nanosheets and 0.5 g of sulfur powder were placed in a crucible respectively, and then the crucible was placed in a tube furnace, the carbon-intercalated molybdenum trioxide nanosheets were placed at the downwind port, facing the heating center, and the sulfur powder was placed at the upwind port; an argon atmosphere was introduced with a flow rate of 200 sccm, and then heated to 500 °C for 1 h; after the reaction was completed, it was naturally cooled to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Prepare a 10 mL sodium chloride solution with a concentration of 5 wt.%; then add 1 g of carbon-intercalated molybdenum disulfide nanosheets into it, mix well, and place in a freeze dryer for 24 h to obtain a carbon-intercalated high-efficiency snow-melting agent.

[0031] The obtained carbon intercalation high-efficiency snow-melting agent was characterized by X-ray diffractometer. Figure 1 The XRD pattern of the final product obtained in this example (MoS2-C) is shown in FIG. Figure 1 It can be seen that the final product is carbon-intercalated molybdenum disulfide.

[0032] The morphology of the carbon intercalation high-efficiency snow melting agent obtained in this example was observed using a scanning electron microscope, and the results are as follows: Figure 2 As shown. Figure 2 It can be seen that the nanosheet size of the carbon intercalated high-efficiency snow-melting agent is 1 μm and the thickness is 200 nm.

[0033] The above test results show that the final product is carbon-intercalated molybdenum disulfide, and the method of the present invention is used to prepare a carbon-intercalated high-efficiency snow-melting agent with a target structure.

[0034] Example 2 The preparation method of the carbon intercalation high-efficiency snow melting agent comprises the following steps: (1) First, 5 mmol of TBAOH was added to 30 mL of ethanol and ultrasonically treated for 10 min to obtain a uniform solution. Then, 1 mmol of MoO3 was added and ultrasonically treated for 30 min. The uniformly mixed solution was heated to 80 °C in an oil bath and stirred for 12 h. After completion, it was cooled to room temperature, washed with ethanol, and dried in a freeze dryer for 24 h to obtain intercalated molybdenum trioxide nanosheets. (2) placing the obtained intercalated molybdenum trioxide nanosheets in an argon atmosphere for heat treatment at an argon flow rate of 100 sccm, heating to 400 °C, and keeping the temperature for 2 h; after completion, naturally cooling to obtain carbon intercalated molybdenum trioxide nanosheets; (3) The obtained carbon-intercalated molybdenum trioxide nanosheets and 1 g of sulfur powder were placed in a crucible respectively, and then the crucible was placed in a tube furnace, the carbon-intercalated molybdenum trioxide nanosheets were placed at the downwind port, facing the heating center, and the sulfur powder was placed at the upwind port; an argon atmosphere was introduced with a flow rate of 200 sccm, and then heated to 400 °C for 2 h; after the reaction was completed, it was naturally cooled to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Prepare a 10 mL sodium chloride solution with a concentration of 5 wt.%; then add 2 g of carbon-intercalated molybdenum disulfide nanosheets into it, mix well, and place in a freeze dryer for 24 h to obtain a carbon-intercalated high-efficiency snow-melting agent.

[0035] Example 3 The preparation method of the carbon intercalation high-efficiency snow melting agent comprises the following steps: (1) First, 3 mmol of DDA was added to 30 mL of ethanol and ultrasonically treated for 10 min to obtain a uniform solution. Then, 1.5 mmol of MoO3 was added and ultrasonically treated for 30 min. The uniformly mixed solution was heated to 80 °C in an oil bath and stirred for 12 h. After completion, it was cooled to room temperature, washed with ethanol, and dried in a freeze dryer for 24 h to obtain intercalated molybdenum trioxide nanosheets. (2) placing the obtained intercalated molybdenum trioxide nanosheets in an argon atmosphere for heat treatment at an argon flow rate of 100 sccm, heating to 400 °C, and keeping the temperature for 2 h; after completion, naturally cooling to obtain carbon intercalated molybdenum trioxide nanosheets; (3) The obtained carbon-intercalated molybdenum trioxide nanosheets and 1.5 g of sulfur powder were placed in a crucible respectively, and then the crucible was placed in a tube furnace, the carbon-intercalated molybdenum trioxide nanosheets were placed at the downwind port, facing the heating center, and the sulfur powder was placed at the upwind port; an argon atmosphere was introduced with a flow rate of 200 sccm, and then heated to 500 °C and kept at this temperature for 1 h; after the reaction was completed, the mixture was cooled naturally to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Prepare a 10 mL sodium chloride solution with a concentration of 7 wt.%; then add 2 g of carbon-intercalated molybdenum disulfide nanosheets into it, mix well, and place in a freeze dryer for 24 h to obtain a carbon-intercalated high-efficiency snow-melting agent.

[0036] Example 4 The preparation method of the carbon intercalation high-efficiency snow melting agent comprises the following steps: (1) First, 1 mmol of AN was added to 30 mL of ethanol and ultrasonically treated for 10 min to obtain a uniform solution. Then, 0.6 mmol of MoO3 was added and ultrasonically treated for 30 min. The uniformly mixed solution was heated to 80 °C in an oil bath and stirred for 12 h. After completion, it was cooled to room temperature, washed with ethanol, and dried in a freeze dryer for 24 h to obtain intercalated molybdenum trioxide nanosheets. (2) placing the obtained intercalated molybdenum trioxide nanosheets in an argon atmosphere for heat treatment at an argon flow rate of 100 sccm, heating to 400 °C, and keeping the temperature for 2 h; after completion, naturally cooling to obtain carbon intercalated molybdenum trioxide nanosheets; (3) The obtained carbon-intercalated molybdenum trioxide nanosheets and 2 g of sulfur powder were placed in a crucible respectively, and then the crucible was placed in a tube furnace, the carbon-intercalated molybdenum trioxide nanosheets were placed at the downwind port, facing the heating center, and the sulfur powder was placed at the upwind port; an argon atmosphere was introduced with a flow rate of 200 sccm, and then heated to 350 °C for 2 h; after the reaction was completed, it was cooled naturally to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Prepare a 10 mL sodium chloride solution with a concentration of 7 wt.%; then add 1 g of carbon-intercalated molybdenum disulfide nanosheets into it, mix well, and place in a freeze dryer for 24 h to obtain a carbon-intercalated high-efficiency snow-melting agent.

[0037] Example 5 The preparation method of the carbon intercalation high-efficiency snow melting agent comprises the following steps: (1) First, 2 mmol of TBAOH was added to 30 mL of ethanol and ultrasonically treated for 10 min to obtain a uniform solution. Then, 0.2 mmol of MoO3 was added and ultrasonically treated for 30 min. The uniformly mixed solution was heated to 80 °C in an oil bath and stirred for 12 h. After completion, it was cooled to room temperature, washed with ethanol, and dried in a freeze dryer for 24 h to obtain intercalated molybdenum trioxide nanosheets. (2) placing the obtained intercalated molybdenum trioxide nanosheets in an argon atmosphere for heat treatment at an argon flow rate of 100 sccm, heating to 400 °C, and keeping the temperature for 2 h; after completion, naturally cooling to obtain carbon intercalated molybdenum trioxide nanosheets; (3) The obtained carbon-intercalated molybdenum trioxide nanosheets and 3 g of sulfur powder were placed in a crucible respectively, and then the crucible was placed in a tube furnace, with the carbon-intercalated molybdenum trioxide nanosheets placed at the downwind port, facing the heating center, and the sulfur powder placed at the upwind port; an argon atmosphere was introduced with a flow rate of 200 sccm, and then heated to 450 °C for 1.5 h; after the reaction was completed, it was cooled naturally to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Prepare a 10 mL sodium chloride solution with a concentration of 7 wt.%; then add 3 g of carbon-intercalated molybdenum disulfide nanosheets into it, mix well, and place in a freeze dryer for 24 h to obtain a carbon-intercalated high-efficiency snow-melting agent.

[0038] Example 6 This example studies the application performance of the carbon intercalation high-efficiency deicing agent prepared in Examples 1-5. According to the test method provided in GB / T 23851-2017 Deicing Agent, the carbon intercalation high-efficiency deicing agent of Examples 1-5 was used as the experimental group, and the sodium chloride deicing agent was used as the comparative group to test its deicing performance and polarization curve in carbon steel. The deicing ability curve of the carbon intercalation high-efficiency deicing agent under different examples is shown in the figure below: Figure 3 The corresponding polarization curve in carbon steel is as shown below: Figure 4 shown.

[0039] Depend on Figure 3 It can be seen that as the amount of carbon intercalated MoS2 increases, the ice melting ability increases. Figure 4 It can be seen that as the amount of carbon intercalated molybdenum disulfide increases, the corrosion resistance becomes stronger; as the concentration of sodium chloride solution increases, the resistance to chloride ion corrosion becomes stronger. It can be seen that carbon intercalated molybdenum disulfide loaded with low concentration of sodium chloride has a high ice melting ability, and as the concentration of sodium chloride solution increases, the resistance to chloride ion corrosion increases.

[0040] Example 7 This embodiment is basically the same as embodiment 1, and the only difference is that this embodiment uses calcium chloride, magnesium chloride, and potassium chloride as chlorine-type salts, and prepares corresponding carbon intercalation high-efficiency snow-melting agents. All kinds of carbon intercalation high-efficiency snow-melting agents made with different chlorine-type salts can achieve the purpose of the present invention, that is, to maintain efficient ice-melting ability under low concentrations of chlorine-type salts, and to slow down the corrosion of chloride ions on pavement and metals. In contrast, the effects of different chlorine-type salts vary. For example, calcium chloride is more likely to absorb moisture and is not as good as sodium chloride in terms of preservation; and the raw material cost of magnesium chloride and potassium chloride will be higher. Sodium chloride is selected as the chlorine-type salt suitable for the present invention because it is cheap, easy to obtain, and has excellent application effects.

[0041] In summary, the present invention utilizes the MoS2 intermediate layer with high oxidation state Mo 4+It has a strong Coulomb force on chloride ions, and realizes the adsorption of chloride ions in chloride-type salts. As a semiconductor, MoS2 can effectively absorb light energy and generate electron-hole pairs, which can improve the photothermal conversion efficiency. It has a fast photothermal response speed, low thermal conductivity, and good stability under photothermal action, which helps to reduce heat loss in photothermal reactions. The present invention utilizes the above-mentioned photothermal conversion characteristics of MoS2 to melt ice, and combines carbonization nuclear reaction to form carbon-intercalated molybdenum disulfide nanosheets, so that the Mo-S bond interlayer spacing is increased, further improving the photothermal conversion efficiency, synergistically enhancing the ice-melting effect, and slowing down the corrosion of chlorine-type snow-melting agents. After the chlorine-type salt of the present invention is loaded on the carbon-intercalated molybdenum disulfide nanosheets, it is not easy to gather between the salts due to adsorption, so that it maintains good dispersibility, and is also convenient for spreading in practical applications.

[0042] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a carbon intercalation high-efficiency snow-melting agent, characterized in that: The steps include: (1) Organic matter and molybdenum trioxide are treated in an oil bath in a solution environment to obtain intercalated molybdenum trioxide nanosheets; (2) Under an inert atmosphere, the intercalated molybdenum trioxide nanosheets are carbonized by heat treatment to obtain carbon-intercalated molybdenum trioxide nanosheets; (3) Under an inert atmosphere, the carbon-intercalated molybdenum trioxide nanosheets react with excess sulfur through heat treatment to obtain carbon-intercalated molybdenum disulfide nanosheets; (4) Adding carbon-intercalated molybdenum disulfide nanosheets to a chloride-type salt solution, and removing the solvent by drying to complete the loading of the chloride-type salt, thereby obtaining a carbon-intercalated high-efficiency snow-melting agent.

2. The method for preparing the carbon intercalation high-efficiency snow-melting agent according to claim 1, characterized in that: In step (1), the organic matter includes at least one of dodecylamine, aniline, and tetrabutylammonium hydroxide; and the molar ratio of the organic matter to molybdenum trioxide is 0.1-1:

1.

3. The method for preparing the carbon intercalation high-efficiency snow-melting agent according to claim 1, characterized in that: In step (2), the inert atmosphere is argon or nitrogen, and the gas flow rate is 10-300 sccm; the heat treatment temperature is 300-500 °C, and the treatment time is 0.5-2 h.

4. The method for preparing the carbon intercalation high-efficiency snow-melting agent according to claim 1, characterized in that: In step (3), the inert atmosphere is argon or nitrogen, and the gas flow rate is 10-300 sccm; the heat treatment temperature is 300-500 °C, and the treatment time is 0.5-2 h.

5. The method for preparing the carbon intercalation efficient snow melting agent according to claim 1, characterized in that: In step (3), the carbon-intercalated molybdenum disulfide nanosheets have a size of 1-2 μm and a thickness of 100-200 nm.

6. The method for preparing the carbon intercalation high-efficiency snow-melting agent according to claim 1, characterized in that: In step (4), the concentration of the chloride salt solution is 1 wt.%-7wt.%.

7. The method for preparing the carbon intercalation efficient snow melting agent according to claim 1, characterized in that: In step (4), the chloride salt of the chloride salt solution includes at least one of sodium chloride, calcium chloride, magnesium chloride and potassium chloride.

8. The method for preparing the carbon intercalation high-efficiency snow-melting agent according to claim 1, characterized in that: Based on the addition amount of 10 mL of chloride salt solution, the addition amount of the corresponding carbon-intercalated molybdenum disulfide nanosheets is 0.1-10 g.

9. The method for preparing the carbon intercalation high-efficiency snow-melting agent according to claim 1, characterized in that: In step (4), freeze drying is used to remove the solvent, so that the chloride salt is loaded and a carbon intercalation high-efficiency snow-melting agent is obtained.

10. A carbon intercalation high-efficiency snow-melting agent, characterized in that: The method is prepared according to any one of claims 1 to 9.